2006
DOI: 10.1007/s10710-006-9014-6
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical particle swarm optimizer for noisy and dynamic environments

Abstract: New Particle Swarm Optimization (PSO) methods for dynamic and noisy function optimization are studied in this paper. The new methods are based on the hierarchical PSO (H-PSO) and a new type of H-PSO algorithm, called Partitioned Hierarchical PSO (PH-PSO). PH-PSO maintains a hierarchy of particles that is partitioned into several sub-swarms for a limited number of generations after a change of the environment occurred. Different methods for determining the best time when to rejoin the sub-swarms and how to hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Janson and Middendorf proposed HPSO, a tree-like structure hierarchical PSO [14], and reported improvements over standard PSO for dynamic environments. They also suggested Partitioned Hierarchical PSO in which a hierarchy of particles is partitioned into several sub-swarms for a limited number of generations after a change in the environment is detected [15]. Lung and Dumitresc [16] used two collaborating populations of equal size, one swarm is responsible for preserving the diversity of the particles by using a crowding differential evolutionary algorithm [17] while the other keeps track of global optimum with a PSO algorithm.…”
Section: Pso In Dynamic Environmentsmentioning
confidence: 99%
“…Janson and Middendorf proposed HPSO, a tree-like structure hierarchical PSO [14], and reported improvements over standard PSO for dynamic environments. They also suggested Partitioned Hierarchical PSO in which a hierarchy of particles is partitioned into several sub-swarms for a limited number of generations after a change in the environment is detected [15]. Lung and Dumitresc [16] used two collaborating populations of equal size, one swarm is responsible for preserving the diversity of the particles by using a crowding differential evolutionary algorithm [17] while the other keeps track of global optimum with a PSO algorithm.…”
Section: Pso In Dynamic Environmentsmentioning
confidence: 99%
“…Li and Dam [28] showed that restricting the information exchange and preventing convergence, increases the diversity of the population and gave better performance when dealing with DE. Janson and Middendorf proposed a hierarchical PSO [22], which showed improvements over the standard PSO for dynamic environments. Lung and Dumitresc [33] used an approach that relied on two different swarms.…”
Section: Related Workmentioning
confidence: 99%
“…Several mechanisms have been introduced to improve the performance of classic PSO in dynamic environments. These mechanisms include adopting the rediversification scheme when a change is detected [8], maintaining the diversity during the run via repulsion [1] or dynamic network topology [21], [29], and multiswarm schemes [28]. These mechanisms are briefly reviewed below.…”
Section: B Pso In Dynamic Environmentsmentioning
confidence: 99%
“…In particular, the investigation of PSO in dynamic environments has become one of the most important applications of SI [2], [21]. However, similar to EAs, classic PSO should be modified to deal with the convergence problem for solving DOPs: Once the swarm has converged, particles lose the ability to track new optima due to the low velocity [2].…”
Section: Introductionmentioning
confidence: 99%